2005
DOI: 10.1017/s0952523805225105
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia can cause sustained hyperglycemia in C57/BL6J mice

Abstract: Effects of anesthesia on the blood glucose of C57/BL6J mice were evaluated under conditions commonly used for testing retinal sensitivity with electroretinographic (ERG) recordings. We evaluated the effects of four anesthetics: nembutal (50 mg/kg), pentothal (100 mg/kg), avertin (240 mg/kg), and ketamine/xylazine (100 mg/kg) using saline as control. We measured blood glucose (BG) levels from tail vein blood before and 15 and 60 min following intraperitoneal injections. Fifteen minutes postinjection, all four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 10 publications
5
48
1
Order By: Relevance
“…Step Care has to be taken when choosing anesthetic for functional studies on islet cells, as several compounds have been reported to exert an effect on blood glucose levels and insulin secretion 23,24 . Isoflurane has been shown to inhibit glucose stimulated insulin release by a direct mechanism on islet cells, and therefore is not suitable for functional studies 25 .…”
Section: Criticalmentioning
confidence: 99%
“…Step Care has to be taken when choosing anesthetic for functional studies on islet cells, as several compounds have been reported to exert an effect on blood glucose levels and insulin secretion 23,24 . Isoflurane has been shown to inhibit glucose stimulated insulin release by a direct mechanism on islet cells, and therefore is not suitable for functional studies 25 .…”
Section: Criticalmentioning
confidence: 99%
“…Anesthesia affects heart rate and blood flow and induces hyperglycemia in mice (Bailey and Flatt, 1980;Brown et al, 2004;Pomplun et al, 2004;Brown et al, 2005;Tanaka et al, 2009). Therefore, assessment of glucose metabolism in anesthetized mice yields results that are not physiological.…”
Section: Anesthesiamentioning
confidence: 99%
“…Some investigators might find that cut-tail sampling is more suitable to their needs and expertise and will perform insulin clamps on anesthetized mice to avoid the confounding effects of stress due to handling. As discussed above, however, anesthesia can affect the metabolism of glucose (Bailey and Flatt, 1980;Brown et al, 2004;Pomplun et al, 2004;Brown et al, 2005). At the very least, investigators performing clamps using the cut-tail sampling method should report indices of stress, such as catecholamine levels or corticosterone levels obtained at the end of a study.…”
Section: Blood Samplingmentioning
confidence: 99%
“…Some anaesthetics lower heart rate and blood flow, which may influence nutrient homeostasis. Whilst, several anaesthetic regimens such as pentobarbital and fentanyl-ketamine-midazolam have been shown to have little effect on either blood glucose or insulin release (Guarino et al 2013, Zuurbier et al 2014, other anaesthetics can cause insulin resistance and hyperglycaemia in both mice and rats (Pomplun et al 2004, Brown et al 2005, Tanaka et al 2009, Guarino et al 2013, Sato et al 2013, which could potentially confound interpretation of experimental data generated using anaesthetised animals. For example isofluorane anaesthesia results in significantly suppressed plasma insulin levels, whilst ketamine-medetomidine-atropine anaesthesia results in almost complete suppression of insulin release and hyperglycaemia (Zuurbier et al 2014).…”
Section: Stress and Anaesthesiamentioning
confidence: 99%